Deferiprone–resveratrol hybrid attenuates iron accumulation, oxidative stress, and antioxidant defenses in iron-loaded human Huh7 hepatic cells - Li, Jin; Koonyosying, Pimpisid; Korsieporn, Woranontee; Paradee, Narisara; Hutachok, Nuntouchaporn; Xu, Honghong; Ma, Yongmin; Chuljerm, Hataichanok; Srichairatanakool, Somdet (Frontiers in Molecular Biosciences, 2024)
Chronic liver diseases are complications of thalassemia with iron overload. Iron chelators are required to remove excessive iron and antioxidants are supplemented to diminish harmful reactive oxygen species (ROS), purposing to ameliorate oxidative liver damage and dysfunctions. Deferiproneresveratrol hybrid (DFP-RVT) is a synthetic iron chelator possessing anti amyloid peptide aggregation, anti-malarial activity, and hepatoprotection in the plasmodium-infected mice. The study focuses on investigating antioxidant, cytotoxicity, iron-chelating, anti-lipid peroxidation and antioxidant-defense properties of DFP-RVT in iron-loaded human hepatocellular carcinoma (Huh7) cells. In the findings, DFP-RVT dose-dependently bound Fe(II) and Fe(III), and exerted stronger ABTS  -and DPPH  -scavenging (IC50 = 8.0 and 164 M, respectively) and anti-RBC hemolytic activity (IC50 = 640 M) than DFP but weaker than RVT (p < 0.01). DFP-RVT was neither toxic to Huh7 cells nor PBMC. In addition, DFP-RVT diminished the level of redox-active iron (p < 0.01) and decreased nonheme iron content (p < 0.01) in iron-loaded Huh7 cells effectively when compared without treatment in the order of DFP-RVT > RVT  DFP treatments (50 µM each). Moreover, the compound decreased levels of hepatic ROS in a dose-dependent manner as well as the level of malondialdehyde, which was stronger than DFP but weaker than RVT. Furthermore, DFP-RVT restored the decrease of GSH content, GPX and SOD activities (p < 0.01) in iron-loaded Huh7 cells in doses-dependent manners, consistently in the order of RVT > DFP-RVT > DFP. Thus, the DFP-RVT hybrid possesses potent iron chelation, antioxidation anti-lipid peroxidation and antioxidant defense against oxidative liver damage under iron overload.